The effects of intermittent negative pressure on the lower extremities' peripheral circulation and wound healing in four patients with lower limb ischemia and hard‐to‐heal leg ulcers: a case report. Issue 20 (26th October 2016) - Sundby, Øyvind H.; Høiseth, Lars Ø.; Mathiesen, Iacob; Jørgensen, Jørgen J.; Sundhagen, Jon O.; Hisdal, Jonny
Abstract: Peripheral circulation is severely compromised in the advanced stages of peripheral arterial disease. Recently, it was shown that the application of −40 mmHg intermittent negative pressure (INP) to the lower leg and foot enhances macro‐ and microcirculation in healthy volunteers. In this case report, we describe the effects of INP treatment on four patients with lower limb ischemia and hard‐to‐heal leg and foot ulcers. We hypothesized that INP therapy may have beneficial hemodynamic and clinical effects in the patients. Four patients (age range: 61–79 years) with hard‐to‐heal leg and foot ulcers (6–24 months) and ankle‐brachial pressure indices of ≤0.60 on the affected side were included. They were treated with an 8‐week intervention period of −40 mmHg INP (10 sec negative pressure and 7 sec atmospheric pressure) on the lower limbs. A custom‐made vacuum chamber was used to apply INP to the affected lower leg and foot for 2 h per day. After 8 weeks of INP therapy, one ulcer healed completely, while the other three ulcers were almost completely healed. These cases suggest that INP may facilitate wound healing. The theoretical foundation is that INP assists wound healing by improving blood flow to the small blood vessels in the affected limb, increasing the flow of oxygen and nutrients to the cells. Abstract : Our results from four patients indicates that intermittent negative pressure applied to the lower leg and foot enhances macro‐and microcirculation and improves wound healing in patients with severe stages of peripheral arterial disease and hard‐to‐heal leg ulcers.